Steady dynamic buckle propagation simulation of confined pipelines under external pressure by user defined elements in ABAQUS. Issue 3 (February 2021) - Yan, Sunting; Ling, Zhangwei; Chen, Yonggui; Jin, Zhijiang
Abstract: This paper simulates steady dynamic buckle propagation of confined linearly elastic pipelines under external pressure by developing a user-defined-element in Abaqus allowing the simulation of dynamic propagation through conventional static step. The simulation is separated into two parts: the static indenting step to deform a pipeline locally and the steady dynamic propagation step to obtain the relationship between the deformation profile and propagation speed.